3SqAir Project: A Living Lab Towards Sustainable Smart Strategy for Indoor Climate Quality Assurance in Classrooms - James Ogundiran; Jean-Paul Kapuya Bulaba Nyembwe; John Omomoluwa Ogundiran; Ruben Alexandre de Souto Santos; Luísa Dias Pereira; Manuel Gameiro da Silva (Atmosphere)
The indoor climate quality in classrooms at the University of Coimbra, Portugal, was investigated as part of the 3SqAir project, supported by the Interreg SUDOE program. This research focused on two equipped classrooms with different ventilation systems: natural and mechanical ventilation. Both classrooms were continuously monitored for IEQ parameters: thermal comfort, indoor air quality, noise, and lighting during heating and cooling seasons. Air temperature, relative humidity, CO2 concentration, particulate matter, nitrogen dioxide, volatile organic compounds, formaldehyde, sound pressure level, and illuminance were measured. Outdoor weather conditions were also recorded. The primary focus was on air temperature, CO2 concentrations, and relative humidity, while air change rates (ACH) were estimated using the Tracer Gas Method. The results showed inadequate thermal conditions in both classrooms, particularly during the heating season. Most weekly mean CO2 concentrations were within acceptable limits, while ACH were below standard recommendations in four CO2 decay phases. Simulations of CO2 decay revealed further air quality gaps in each room. Corrective measures within the 3SqAir project framework were suggested for approval and implementation while monitoring continues. This work represents the first phase in an evolving study towards developing sustainable strategies for improving indoor air quality in classrooms.